Mobile application to qualify nursing care of patients with type 1 Diabetes mellitus (Research, Society and Development, 2022)
Diabetes Mellitus (DM) is a growing global health problem. The nurse is responsible for educating the patient and groups involved with the child with type 1 Diabetes Mellitus (DM1). Mobile applications (Apps) for guidance in health work can be useful as a complementary way to access information. This study presents the building process of a mobile application prototype called DICABETES, Professional Master's product in the field of Teaching in Health. This is an experience report written based on Charles Maguerez's Arc, which underpins and aids the development of critical thinking. Pediatric nurses participated in the requirements specification stage. The evaluation of the product was carried out through the Scale Usability Score (ScSUS), and it was performed by eleven treating nurses, two specialists with recognized professional practice in DM and three professionals in the area of Information Technology. The results indicate that, despite the need for improvements, the DICABETES product presented a satisfactory experience, showing good effectiveness and efficiency. Thus, it is intended to improve the application in order to make it available as an educational product for use by healthcare professionals and for the daily practice of patient care.